Electrosynthesized CuOx/graphene by a four-electrode electrolysis system for the oxygen reduction reaction to hydrogen peroxide. Issue 34 (29th March 2021) - Xiao, He; Li, Bo; Zhao, Man; Li, Ya; Hu, Tianjun; Jia, Jianfeng; Wu, Haishun
Abstract : A facile four-electrode electrolysis system is firstly applied to synthesize CuO x /graphene hybrid for oxygen reduction to hydrogen peroxide. Abstract : Here a facile four-electrode electrolysis system is firstly applied to synthesize a CuO x /graphene hybrid. The exfoliation of graphite via high electrolytic voltage and dissolution of copper via low electrolytic voltage are achieved simultaneously. CuO x /G with the highest content of CuO x shows superior electrocatalytic activity for oxygen reduction to hydrogen peroxide.